Evaluating Acute Toxicity of Jamu Cekok in Rats: A Histopathological Approach Based on OECD 425 - Michelle The; Puji Astuti; Siti Aisyah; Hadi Kurniawan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Jamu cekok, an Indonesian traditional medicine to increase children appetite, has not passed preclinical or clinical trials. The rhizomes that make up jamu cekok such as pakai bahasa latinnya contain ethyl p-methoxycinnamate which is toxic, thus potentially harmful to the children. Therefore in this study we aim to determine the Lethal Dose (LD50) value of jamu cekok using the OECD 425 method as well as to observed the histopathological change in the liver in female Rattus norvegicus L. This study used an analytical experimental design with the OECD 425 method to test the acute toxicity of jamu cekok. The test rats used were in accordance with the OECD 425 protocol with an additional 2 negative control rats. Jamu cekok in the form of decocta were given once on the first day of the acute toxicity test and observed for 14 days. On the 15th day, rats were euthanized, dissected, and hepatic organs were taken to make histopathological preparations with Hematoxylin-Eosin staining. Analysis of hepatic damage was assessed using Histopathology Scoring Manja Roenigk and tested by Kruskal Wallis method. The results showed the LD50 value of decocta extract of jamu cekok was >5000 mg/kgBB. Observations of body weight, behavioral tests, organ index, and macroscopic hepar of test rats showed no signs of toxicity. However, The statistical analysis for histopathology test showed that there was a significant difference (p<0.05) between the negative control group and the 5000 mg/kgBB treatment group. In conclusion, the administration of jamu cekok was categorized as practically non-toxic but it can caused reversible hepatic damage at a dose of 5000 mg/kgBB.